2019
DOI: 10.9734/ijtdh/2019/v35i430131
|View full text |Cite
|
Sign up to set email alerts
|

Human Contamination and Schistosome Infection Intensity in Bulinid and Planorbid Snail Vectors in Kadawa Irrigation Area, Kano State, Nigeria

Abstract: Objectives of the Study: An Epidemiological Research, a cross-sectional study, was conducted to determine the magnitude of human contamination of irrigation canal perimeter as it relates to the prevalence and intensity of schistosome cercarial infection in snail vectors. Place and Duration of Study: The study was conducted along water canal located within an irrigation area, Kano River Project Phase I, Kadawa, between January and June, 2012. Methodology: The study area was categorized into Zone of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…This supports the findings of Ahmed and Bassey [16] who reported the involvement of males in open defecation in the study area and that school-age children tend to urinate indiscriminately while swimming or playing in the water. It was observed that human behaviour towards environmental contamination and lack of measures to improve sanitary conditions continue to predispose individuals to infection and reinfection in endemic communities [9,40]. In some rural communities, unhygienic methods of disposing human excreta create favourable conditions for the snail intermediate hosts to thrive [41].…”
Section: Environmental Contamination and Healthcare-seeking Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the findings of Ahmed and Bassey [16] who reported the involvement of males in open defecation in the study area and that school-age children tend to urinate indiscriminately while swimming or playing in the water. It was observed that human behaviour towards environmental contamination and lack of measures to improve sanitary conditions continue to predispose individuals to infection and reinfection in endemic communities [9,40]. In some rural communities, unhygienic methods of disposing human excreta create favourable conditions for the snail intermediate hosts to thrive [41].…”
Section: Environmental Contamination and Healthcare-seeking Behaviourmentioning
confidence: 99%
“…In Nigeria, the most populous country in Africa and with significant number of water resources development projects, schistosomiasis is endemic with transmission influenced by several factors such as continuous water contact activities for socioeconomic purposes and anthropogenic faecal and urine contamination [9], coupled with prevailing snail vector abundance in endemic areas [10,11]. At least 91.4% of the population requiring treatment for schistosomiasis live in Africa [3].…”
Section: Introductionmentioning
confidence: 99%